On the spatially periodic ordering in the system of electrons above the surface of liquid helium in an external electric field - Lytvynenko, D.M.; Slyusarenko, Yu.V.; Kirdin, A.I. (Condensed Matter Physics, 2018)
A theory of equilibrium states of electrons above a liquid helium surface in the presence of an external clamping
field is built based on the first principles of quantum statistics for the system of many identical Fermi-particles.
The approach is based on the variation principle modified for the considered system and on Thomas-Fermi
model. In terms of the developed theory we obtain the self-consistency equations that connect the parameters
of the system description, i.e., the potential of a static electric field, the distribution function of electrons and
the surface profile of a liquid dielectric. The equations are used to study the phase transition of the system to
a spatially periodic state. To demonstrate the capabilities of the proposed method, the characteristics of the
phase transition of the system to a spatially periodic state of a trough type are analyzed. Побудовано теорiю рiвноважних станiв електронiв над поверхнею рiдкого гелiю у зовнiшньому притискаючому полi на основi перших принципiв квантової статистики для систем багатьох тотожних Фермi
частинок. В основу пiдходу покладено варiацiйний принцип, модифiкований для розглянутих систем, i
модель Томаса-Фермi. В термiнах розвиненої теорiї отриманi рiвняння самоузгодження, що пов’язують
параметри опису такої системи — потенцiал статичного електричного поля, функцiю розподiлу зарядiв
i профiль поверхнi рiдкого дiелектрика. Цi рiвняння використано для вивчення фазового перетворення
системи до просторово-перiодичних станiв. Як приклад можливостей запропонованого методу, аналiзуються характеристики фазового перетворення системи до просторово-перiодичних станiв жолобкового
типу.